Anorectal Manometric Studies in Patients with Symptomatic and Asymptomatic Rectocele - Fukuzawa, Masahiro; Ikeda, Tarou; Hagiwara, Noritsugu; Tomita, Ryouichi; Fujisaki, Shigeru; Igarashi, Seigio (Nippon Shokaki Geka Gakkai zasshi, 2000)
To clarify the cause of rectocele, the anorectal functions in patients with rectocele were inventigated. Anorectal manometric studies were performed in 38 patients with symptomatic rectocele (A group; all women, aged 22-79 years with a mean age of 52.8 years), 16 patients with asymptomatic rectocele (B group; all women, aged 37-74 years with a mean age of 50.6 years), and control subjects (C group; all women, aged 16-69 years with a mean age of 48.6 years). There were no differences in the results between the A and B groups. Anorectal manometric studies revealed a higher incidence of anal sphincter dysfunction (lower resting and voluntary contraction pressure), rectal capacity dysfunction (decrease of compliance). and rectal sensory dysfunction (increase of sensory threshold volume and minimum tolerated volume) in group A and B patients as compared with group C patients. These results, namely, the decrease of rectal compliance and high rectal pressure, could cause symptomatic and asymptomatic rectocele.